Let $(z_n)$ be a sequence of complex numbers. If $\sum_{n=1}^\infty \vert z_n\vert$ converges then $\sum_{n=1}^\infty z_n$ does too.

Show that this statement is true assuming we know this is true for real series.

Let $z_n=a_n+ib_n$ where $(a_n)$ and $(b_n)$ are real sequences. Then

\begin{align} \sum_{n=1}^\infty \vert z_n\vert &= \sum_{n=1}^\infty \vert a_n + ib_n \vert \\ &\ge \sum_{n=1}^\infty \Big[\vert a_n \vert - \vert b_n \vert\Big] \\ &= \sum_{n=1}^\infty \vert a_n \vert - \sum_{n=1}^\infty\vert b_n \vert \end{align}

So if the infinite series of $\vert z_n\vert$ converges then $\vert a_n\vert$ and $\vert b_n\vert$ converge. Now also note that

$$\sum_{n=1}^\infty z_n = \sum_{n=1}^\infty a_n + i\sum_{n=1}^\infty b_n.$$

Since the infinite series of $|a_n|$ and $|b_n|$ converge, then the infinite series of $a_n$ and $b_n$ converge. Hence

$$\sum_{n=1}^\infty z_n$$


Is this a sufficient proof?


1 Answer 1


No, it's not. Having three sequences, $r_n,s_n,t_n$ where $r_n$ converges, we cannot conclude from $r_n\geq s_n-t_n$ that $s_n$ and $t_n$ converge. For example, let $r_n=2$, $s_n=n+1$ and $t_n=n$. See what happens there?

But we can prove it by doing the following. \begin{align} \sum_{n=1}^{\infty}|z_n|&=\sum_{n=1}^{\infty}|a_n+ib_n|\\ &= \sum_{n=1}^{\infty}\sqrt{a_n^2+b_n^2}\\ &\geq\sum_{n=1}^{\infty}\sqrt{a_n^2+0}\\ &=\sum_{n=1}^{\infty}|a_n| \end{align} We can do the same to show $|b_n|$ converges, and then we can proceed to reason the way you did, for the last part of your proof was correct.


You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .